Pengaruh Teori Technology Acceptance Model, Religiusitas Dan Sikap Terhadap Niat Investor Berinvestasi Pada Saham Syariah Di Indonesia - Riri Putri Dika (ITB AAS INDONESIA Surakarta, 2023)
The emergence of sharia investment products in the Indonesian capital market opens up opportunities for Indonesian Muslims to invest. At present, the growth of investors in Islamic stock investment has not developed significantly. Sharia Online Trading System (SOTS) is the first system in the world developed to facilitate sharia investment in conducting stock transactions in accordance with sharia principles. This study aims to examine the factors that influence the intention to invest in sharia shares in Indonesia with attitude as mediation using the Technology Acceptance Model (TAM) theory using a questionnaire in data collection. The population in this study comes from data on Islamic stock investors in Indonesia with a total of 382 respondents and the data was analyzed using descriptive SEM-PLS research. The results of the study found that there was an influence perceived ease of use, religiosity, investor attitudes towards investment intentions in sharia shares. Perceived ease of use, religiosity had an effect on attitudes. The perceived usefulness does not show an influence on investor attitudes and there is also no effect of the perceived usefulness on the intention to invest in sharia shares. Variables perceived ease of use and religiosity using attitude as mediation, a positive influence was found, but not with perceived usefulness in attitude as mediation on the intention to invest in sharia stocks.